Teaching English in rural settings: A systematic review of challenges and strategies in non-technological classrooms - Candrawati, Andi Cahyuni; Purbani, Widyastuti (Universitas Ahmad Dahlan, 2025)
The aim of this study is to understand what challenges encountered by English teachers and how they cope with the barriers, particularly in low-resource, non-technological settings. Using the PRISMA framework, this study conducted a systematic literature review to synthesize the twenty articles published between 2018 and 2024 from Scopus, Connected Papers and ERIC. This study identified eight major challenges which are: inadequate resources for learning, poor school infrastructure, lack of teaching media, overly teacher-centered pedagogy, heavy workload, insufficiency of prepared teachers, adaptation issues, and low levels of student motivation. To cope with these challenges, teachers applied six primary strategies which included development of teaching materials by hand, content simplification through local dialects, application of teacher-centered pedagogy, peer collaboration, curriculum improvisation to fit local context, and informal professional development activities. These results have noted the creativity and adaptability of teachers within constrained environments and underscore the necessity for situated educational policies. Moreover, the study contributes to a better understanding on the preservation of English instruction in rural settings and offers useful information to policy makers, educators, and other divisions which work towards resolving inequities in education.